Analysis of Intellectual Intelligence (IQ) and Emotional Intelligence (EQ) on Employee Performance with Spiritual Intelligence (SQ) as a mediating variable - Alpisarrin, Alpisarrin; Panorama, Maya; Maftukhatusolikhah, Maftukhatusolikhah (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This research starts from the problem of whether Intellectual Intelligence (IQ) and Emotional Intelligence (EQ) affect employee performance with Spiritual Intelligence (SQ) as a mediating variable. This research aims to determine and analyze the influence of Intellectual Intelligence (IQ) and Emotional Intelligence (EQ) on employee performance with Spiritual Intelligence (SQ) as a mediating variable. This type of research is quantitative research with correlational problem construction. This quantitative research takes the form of numbers and is analyzed using statistics. The population in this study were employees of the distribution department of PT Saribumi Sriguna Putra, Palembang City, PT Sriguna Patra Niaga, and PT Graha Patra Saribumi in 2023, totaling 105 people. The sample in this study was taken using a saturated sampling technique, namely a sample determination technique when all members are used as samples. Thus, the sample in this study was taken equal to the population, namely 105 people. The data analysis technique in this research uses the SPSS application. factors such as intellectual intelligence, emotional intelligence and spiritual intelligence affect the creation of employee performance, and spiritual intelligence is able to mediate between intellectual intelligence factors, emotional intelligence and employee performance. the findings in this study are that this research is expected to be a view for company owners to pay more attention to factors to improve maximum employee performance.